2014
DOI: 10.1097/mpa.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Malignancy With Endoscopic Ultrasonography in Patients With Branch Duct–Type Intraductal Papillary Mucinous Neoplasm

Abstract: Objective: We evaluated the accuracy of a new endoscopic ultrasonography (EUS) scoring system to predict malignancy in branch duct-type intraductal papillary mucinous neoplasms (BD-IPMNs).Methods: We performed a retrospective multicenter study of patients who underwent EUS within 3 months before surgery and were diagnosed as having BD-IPMNs by postoperative pathologies at 8 hospitals in Korea from August 2002 to December 2011. To predict the malignancy, we applied the EUS scoring system consisting of pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Present clinical and imaging criteria for assessing malignant risk in IPMN are not wholly accurate 57 and could be improved through the further use of robust molecular or protein-based biomarkers. Our findings here and those of prior studies indicate that increased expression of Plectin-1 is a molecular harbinger of malignant progression that might be suitably leveraged for the clinical assessment of IPMN either prior to and after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present clinical and imaging criteria for assessing malignant risk in IPMN are not wholly accurate 57 and could be improved through the further use of robust molecular or protein-based biomarkers. Our findings here and those of prior studies indicate that increased expression of Plectin-1 is a molecular harbinger of malignant progression that might be suitably leveraged for the clinical assessment of IPMN either prior to and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential risks associated with surgery 3,4 , significant efforts have been made to define robust clinical and imaging criteria that accurately differentiate malignant/high risk IPMNs requiring surgical resection from benign/low risk IPMNs that can be managed conservatively. While established guidelines are useful in stratifying risk, they still do not accurately identify all patients who do or do not require surgery 57 , highlighting the need for additional criteria such as biomarkers to improve diagnostic accuracy 811 . One such promising biomarker is Plectin-1, previously shown to be expressed at later stages of pancreatic neoplastic progression, including high grade pancreatic intraepithelial neoplasia and most invasive PDAs 12,13 , as well as in malignant IPMNs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…More studies are needed using the newer MRI machines. A recent multicenter study from Korea examined 84 resected BD-IPMNs in order to evaluate EUS predictors of malignancy in BD-IPMNs [28] . An EUS scoring system (0-10) was developed in which points were assigned based on cyst size, mural nodules, pancreatic duct dilation, thick septa and the characteristic "patulous" papilla [28] .…”
Section: Eus Morphologymentioning
confidence: 99%
“…A recent multicenter study from Korea examined 84 resected BD-IPMNs in order to evaluate EUS predictors of malignancy in BD-IPMNs [28] . An EUS scoring system (0-10) was developed in which points were assigned based on cyst size, mural nodules, pancreatic duct dilation, thick septa and the characteristic "patulous" papilla [28] . This scoring system was found to have an overall area under the curve of 0.944 with 75% sensitivity and 94% specificity for malignant BD-IPMN using an EUS score cutoff of ≥ 7.…”
Section: Eus Morphologymentioning
confidence: 99%
“…However, a study showed that not all imaging features of the cysts should be weighted equally for assessing the malignancy of IPMN (8). The International Consensus Guidelines suggest that pancreatic cysts with "worrisome features" and cysts larger than 3 cm without "worrisome features" should be further evaluated by endoscopic ultrasonography (EUS) (2), which improves the accuracy of differentiating benign from malignant IPMNs (9). However, EUS is known to present difficulties because of its operator dependence and its low negative predictive value for fine-needle aspiration cytology (10).…”
mentioning
confidence: 99%